Biofilm Formation and Motility Are Promoted by Cj0588-Directed Methylation of rRNA in Campylobacter jejuni - Sałamaszyńska-Guz, Agnieszka; Rose, Simon; Lykkebo, Claus A.; Taciak, Bartłomiej; Bącal, Paweł; Uśpieński, Tomasz; Douthwaite, Stephen (Frontiers in Cellular and Infection Microbiology, 2018)
Numerous bacterial pathogens express an ortholog of the enzyme TlyA, which is an rRNA 2´-O-methyltransferase associated with resistance to cyclic peptide antibiotics such as capreomycin. Several other virulence traits have also been attributed to TlyA, and these appear to be unrelated to its methyltransferase activity. The bacterial pathogen Campylobacter jejuni possesses the TlyA homolog Cj0588, which has been shown to contribute to virulence. Here, we investigate the mechanism of Cj0588 action and demonstrate that it is a type I homolog of TlyA that 2´-O-methylates 23S rRNA nucleotide C1920. This same specific function is retained by Cj0588 both in vitro and also when expressed in Escherichia coli. Deletion of the cj0588 gene in C. jejuni or substitution with alanine of K80, D162 or K188 in the catalytic center of the enzyme cause complete loss of 2´-O-methylation activity. Cofactor interactions remain unchanged and binding affinity to the ribosomal substrate is only slightly reduced, indicating that the inactivated proteins are folded correctly. The substitution mutations thus dissociate the 2´-O-methylation function of Cj0588/TlyA from any other putative roles that the protein might play. C. jejuni strains expressing catalytically inactive versions of Cj0588 have the same phenotype as cj0588-null mutants, and show altered tolerance to capreomycin due to perturbed ribosomal subunit association, reduced motility and impaired ability to form biofilms. These functions are reestablished when methyltransferase activity is restored and we conclude that the contribution of Cj0588 to virulence in C. jejuni is a consequence of the enzyme’s ability to methylate its rRNA.